The Effect of the Internalization of Tarjih Verdict on the Practice of Ablution and Prayer of Muhammadiyah Residents PCM Pucuk - Mubarok Mubarok; M. Mubin mubin; Moh. Sholeh; Imam Prihardiyanto; Muhammad Alfi Syahrin (PT. Education Research Center, 2026)
This study aims to analyze the influence of the Intensity of the Study of the Tarjih Decision Association (HPT) and the Internalization of Tarjih Decision on the Practice of Ablution and Prayer of Muhammadiyah residents at PCM Pucuk Lamongan. This study uses a quantitative approach with a survey method. The research sample amounted to 100 respondents, and the data were analyzed using multiple linear regression with the help of SPSS version 26. The results showed that the intensity of HPT Study and the Internalization of Tarjih Verdicts simultaneously had a positive and significant effect on the practice of Ablution and Prayer, with an F value of 78.114 and a significance of p < 0.001. The R Square value of 0.611 indicates that 61.1% of the variation in the practice of Ablution and Prayer can be explained by these two variables, while the remaining 38.9% is influenced by other factors outside the research model. Partially, the intensity of the HPT study had a positive and significant effect on the practice of ablution and prayer with a regression coefficient of 0.421, a t-value of 5.198, and p < 0.001. The internalization of the Tarjih Decision also had a positive and significant effect with a regression coefficient of 0.536, a t-value of 5.718, and p < 0.001. This finding confirms that the effectiveness of HPT in shaping the practice of community worship is not only determined by the intensity of the study, but also by the depth of internalization of the value of tarjih in the religious life of Muhammadiyah residents.